2016
DOI: 10.1504/ijltm.2016.077129
|View full text |Cite
|
Sign up to set email alerts
|

'Value for money' and the restaurant experience: a case study of supply and demand stakeholders

Abstract: Using the case of a training restaurant open to paying guests, this study compares the perceptions of two groups of stakeholders with regard to different factors of the dining experience. The first group represents the supply side and is composed of 73 students involved in the preparation and delivery of menu dishes, while the demand side consists of 222 guests of the training restaurant. Both groups' level of agreement was similar when they identified gaps regarding the restaurant's performance in terms of dé… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In the restaurant context, Voon (2012) found that the most important factor determining youth loyalty is the value for money. Alonso et al (2016) captured the perceptions of different stakeholder groups through their detailed study on the value of money and the restaurant experience. Soriano (2002) acknowledged that restaurateurs should go beyond providing high quality food and service and should focus on providing additional value to the customer in order to attract and retain customers.…”
Section: Value For Moneymentioning
confidence: 99%
“…In the restaurant context, Voon (2012) found that the most important factor determining youth loyalty is the value for money. Alonso et al (2016) captured the perceptions of different stakeholder groups through their detailed study on the value of money and the restaurant experience. Soriano (2002) acknowledged that restaurateurs should go beyond providing high quality food and service and should focus on providing additional value to the customer in order to attract and retain customers.…”
Section: Value For Moneymentioning
confidence: 99%
“…Despite the importance of RL in the restaurant sector (Elkhwesky et al , 2022a), there are very few studies that deal with this term per se . Most of the extant research has focused on individual RL practices, such as CSR, stakeholder involvement, ethics, sustainability and environmentally friendly actions (Alonso et al , 2016; Iaquinto, 2014; Kasim and Ismail, 2012; Kim and Brymer, 2011; Lee and Heo, 2009; Raab et al , 2018; Radwan et al , 2010; Swimberghe and Wooldridge, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%